UH-1N Category II Arctic Tests. - Ford, James A.; Nelson, Gary L. (1972)
The UH-1N was evaluated for operational use in an arctic environment. With few exceptions it was found that the UH-1N could be operated and maintained satisfactorily in the arctic environment. The engines operated satisfactorily under the conditions tested, and no stalling or unusual characteristics were observed after hovering over areas of heavy snow concentration. Hydraulic and flight control systems were considered excellent and very suitable for extreme cold weather operations, but the rotor brake was unsatisfactory. The communications systems showed marked improvement as a result of incorporating T.O. 1H-1(U)N-506. UHF-AM and VHF-AM radios, in particular were suitable for extended range use. (Author) Includes addendum.